2013
DOI: 10.1063/1.4775726
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the laser pulse shape to improve the quality of the self-injected electron beam in laser wakefield acceleration

Abstract: In laser wakefield acceleration, tailoring the shape of the laser pulse is one way of influencing the laser-plasma interaction and, therefore, of improving the quality of the self-injected electron beam in the bubble regime. Using three-dimensional particle-in-cell simulations, the evolution dynamics of the laser pulse and the quality of the self-injected beam, for a Gaussian pulse, a positive skew pulse (i.e., one with sharp rise and slow fall), and a negative skew pulse (i.e., one with a slow rise and sharp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Several remedies have been suggested to address this issue, such as working just above the injection threshold, optimizing laser parameters such as pulse length and spotsize and tailoring the laser pulse shape [17,18]. These do improve the beam quality to some extent, producing an energy spread of around 3%.…”
Section: Introductionmentioning
confidence: 99%
“…Several remedies have been suggested to address this issue, such as working just above the injection threshold, optimizing laser parameters such as pulse length and spotsize and tailoring the laser pulse shape [17,18]. These do improve the beam quality to some extent, producing an energy spread of around 3%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, controlling the FRS and the wakefields is essential for controlling the charge, energy, and quality of the electron beam in this regime. It has been suggested that by introducing a chirp in the laser pulse, the growth of FRS can be controlled [21][22][23] along with the wakefield amplitude and the electron beam parameters in the laser wakefield electron acceleration [24][25][26][27]. However, there are only a few experimental studies on the effect of frequency chirped laser pulses on electron acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…If we calculate the electron cyclotron frequency corresponding to the observed magnetic field in present PIC simulations, we find that it is less than the plasma electron frequency even if the magnetic field is more than 100 T. This justifies the well resolved simulation results for the used grid dimensions and particle per cell. 50,52 The simulation time step was 1:65 Â 10 À16 s, which satisfies the Courant condition marginally so that the numerical dispersion is as small as possible. To resolve laser pulse and plasma fluctuations, we used five particles per cell for present set of simulations.…”
Section: Pic Simulation Detailsmentioning
confidence: 99%